2013
DOI: 10.1186/1471-2148-13-84
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of the genus Cymbidium: lights into the species identification, phylogenetic implications and population genetic analyses

Abstract: BackgroundCymbidium orchids, including some 50 species, are the famous flowers, and they possess high commercial value in the floricultural industry. Furthermore, the values of different orchids are great differences. However, species identification is very difficult. To a certain degree, chloroplast DNA sequence data are a versatile tool for species identification and phylogenetic implications in plants. Different chloroplast loci have been utilized for evaluating phylogenetic relationships at each classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
286
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(302 citation statements)
references
References 76 publications
15
286
1
Order By: Relevance
“…Studies by Guisinger et al (2010) showed that while Poaceae genera either lack accD, ycf1, and ycf 2 genes entirely or have lost all except remnants of these genes, Typha latifolia (Typhaceae, Poales) retains them. Yang et al (2013) sequenced five Cymbidium Sw. species and found that unlike Phalaenopsis the Cymbidium species retained most of their ndh genes although only a few of these retained genes were functional. Studies on the palm family (Arecaceae, Arecales) have revealed a plastid genome that is typical for angiosperms, although ycf1 was determined to be a pseudogene in the family .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Guisinger et al (2010) showed that while Poaceae genera either lack accD, ycf1, and ycf 2 genes entirely or have lost all except remnants of these genes, Typha latifolia (Typhaceae, Poales) retains them. Yang et al (2013) sequenced five Cymbidium Sw. species and found that unlike Phalaenopsis the Cymbidium species retained most of their ndh genes although only a few of these retained genes were functional. Studies on the palm family (Arecaceae, Arecales) have revealed a plastid genome that is typical for angiosperms, although ycf1 was determined to be a pseudogene in the family .…”
mentioning
confidence: 99%
“…Orchidaceae are early diverging within Asparagales (Pires et al 2006;Seberg et al 2012;Chen et al 2013) and are estimated to have a stem node age of 95.7 MYA and a crown node age of 51.6 MYA (Chen et al 2013). The orchid plastid genomes investigated to date lack all or some of their ndh genes or coding functions (Chang et al 2006;Wu et al 2010;Pan et al 2012;Yang et al 2013) and are unlikely to be typical for other members of Asparagales such as Iridaceae.…”
mentioning
confidence: 99%
“…The SC/IR boundaries showed only slight differences, for example, at ycf1 and ѱycf1 (Figure 4). This phenomenon is relatively common in other cp genomes [8,16,21]. Several genes, including ndhF, rps19, and trnH, had almost identical locations and sizes among Fritillaria.…”
Section: Discussionmentioning
confidence: 80%
“…The cp genome ranges from 120 to 180 kb in higher plants and has a quadripartite structure consisting of a large single copy (LSC) and small single copy (SSC) region and two copies of a larger inverted repeat (IR) [7]. The cp genome encodes 110 to 130 genes with up to 80 unique protein-coding genes, four ribosomal RNAs (rRNAs), and approximately 30 transfer RNAs (tRNAs) [8,9]. However, a few parasitic plants have small chloroplast genomes due to unique life cycles [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that chloroplast DNA contains a great deal of genetic variation between species and populations (Wojciechowski et al, 2004;Byrne and Hankinson, 2012;Yang et al, 2013). Non-coding areas of SC regions are frequently used in phylogenetic analysis of lower plants (Clegg et al, 1994).…”
Section: Introductionmentioning
confidence: 99%